Respostas
respondido por:
2
f(x) = x^2 - 3x - 10
f(-1) = (-1)^2 - 3.(-1) - 10
= 1 + 3 - 10
= 4 - 10
= -6
f(-1) = (-1)^2 - 3.(-1) - 10
= 1 + 3 - 10
= 4 - 10
= -6
santosdellmiva:
muito obg
respondido por:
0
Boa tarde!
f(x) = x² - 3x - 10
f(-1)
f(-1) = (-1)² - 3.(-1) - 10
f(-1) = 1 + 3 - 10
f(-1) = 4 - 10
f(-1) = - 6
Bons estudos!
f(x) = x² - 3x - 10
f(-1)
f(-1) = (-1)² - 3.(-1) - 10
f(-1) = 1 + 3 - 10
f(-1) = 4 - 10
f(-1) = - 6
Bons estudos!
Perguntas similares
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás